Healthy Colleges: The Role of the Environment in Students’ Mental Well-Being - Berrío-Quispe, Margoth Luliana; Senepo-Gonzales, Angélica; Espíritu-Martinez, Antony Paul; Bedoya-Ávalos, José Rolando; Curro-Urbano, María; Pérez-Vargas, Reina; Ramírez-Rodríguez, Wilman Xavier; Casanueva-Yáñez, Galvarino (Journal of Ecohumanism, 2024)
This study, conducted at a university in Lima, explores the relationship between the university environment and students’ mental health. With a quantitative approach, two Likert-type questionnaires were applied to a non-probabilistic sample of 140 students. The variables analyzed included four dimensions of the environment: campus design and architecture, facilities and resources, physical environment, and safety and well-being, in relation to various facets of mental health, such as emotional, social, academic, and psychological well-being. The results indicated that a well-designed and maintained university environment, with adequate facilities and a safe environment, is associated with greater mental well-being among students. Significant correlations were found between positive perceptions of the environment and better mental health indicators, especially in the reduction of anxiety and the improvement of emotional well-being. The study’s conclusion underscores the importance of a comprehensive approach in the design and maintenance of the university environment to promote students’ mental well-being, suggesting that universities should prioritize these aspects to foster a healthy and supportive educational environment.